Draft genome sequence of carbapenem-resistant Shewanella algae strain AC isolated from small abalone (Haliotis diversicolor). (September 2018) - Huang, Yao-Ting; Cheng, Jan-Fang; Chen, Shi-Yu; Hong, Yu-Kai; Wu, Zong-Yen; Liu, Po-Yu
Abstract: Objectives: Shewanella algae is an environmental marine bacterium and an emerging opportunistic human pathogen. Moreover, there are increasing reports of strains showing multidrug resistance, particularly carbapenem-resistant isolates. Although S. algae has been found in bivalve shellfish aquaculture, there is very little genome-wide data on resistance determinants in S. algae from shellfish. The aim of this study was to determine the whole genome sequence of carbapenem-resistant S. algae strain AC isolated from small abalone in Taiwan. Methods: Bacterial genomic DNA was sequenced using an Illumina MiSeq platform with 250-bp paired-end reads. De novo genome assembly was performed using Velvet v.1.2.07. The whole genome was annotated and several candidate genes for antimicrobial resistance were identified. Results: The genome size was calculated at 4 751 156 bp, with a mean G + C content of 53.09%. A total of 4164 protein-coding sequences, 7 rRNAs, 85 tRNAs and 5 non-coding RNAs were identified. The genome contains genes associated with resistance to β-lactams, trimethoprim, tetracycline, colistin and quinolones. Multiple efflux pump genes were also detected. Conclusion: Small abalone is a potential source of foodborne drug-resistant S. algae . The genome sequence of carbapenem-resistant S. algae strain AC isolated from small abalone will provide valuable information for further study of the dissemination of resistance genes at the human–animal interface.